Implementasi Algoritma K- Harmonic Means Untuk Penyusunan Tata Letak Data Buku Perpustakaan - Nasution, Fadillah Fikri Zaman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
MIN 3 Deli Serdang is a public school located at Jalan Mesjid, Beringin Village. MIN 3 Deli Serdang provides education for elementary school (SD) and the learning time of MIN 3 Deli Serdang is held from morning to afternoon. Many facilities are provided at MIN 3 Deli Serdang school, from teaching equipment, field and library. In the Deli Serdang library there are many books that can be read from grade 1 to grade 6, the books provided are in accordance with the education provided. Some problems in the preparation of the layout are students who read books according to their interests and complete assignments given by the teacher, books that are read only on the nearest shelf this is because the library guard cannot arrange the layout of books that are often used by students every day according to their needs considering that there are many books to read. This research uses the K-Harmonic Means method for the preparation of library book data layout at MIN 3 Deli Serdang school. With the implementation of the K-Harmonic Means method, the MIN 3 Deli Serdang library can easily arrange the layout of book data.